THE HYPERBOLIC EXPRESSION IN LANGSTON HUGHES' POEMS - Wuda, Ermelinda; Wanggai, Febe F I (Lantern: Journal of Language and Literature, 2024)
This study aimed to determine the forms of hyperbole based on Claridge theory, denotative and connotative meaning, and function of hyperbole found in Langston Hughes’s poem. This study used the descriptive qualitative method. The data was taken from a collection of poetry by Langston Hughes, in the form of lines, words, phrases, sentences, and stanzas. The result of the research shows that from four poems, it is found 17 hyperbolic expressions in Langston Hughes’s poems texts. These hyperbolic expressions are grouped into five forms. They are 2 single-word hyperbole, 6 phrasal hyperbole, 2 clausal hyperbole, 2 numerical hyperbole, and 5 comparison hyperbole. This study also analyzes the meaning of denotative and connotative and the function of hyperbolic expressions which are emphasize, evaluation, simplification, interest intensification, contrast of differences, and clarification. Key words: Poetry, Figurative Language, Hyperbole